Determination of demographic and socio-economic factors influencing clean cooking fuel adoption in rural Bangladesh: Demographic and socio-economic factors on clean cooking fuel - Shabnam, Dilruba; Girling, Laura (SAARC Journal of Agriculture, 2022)
Biogas as a clean source of cooking fuel has enormous potential to meet Bangladesh's energy needs. The objective of this article is to identify the factors influence biogas adoption in rural households. The study aimed to look at the policy framework that needs to be put in place to promote biogas adoption as a cooking fuel in the study region. This study collected primary data by interviewing 118 respondents with a structured questionnaire (78 biogas users and 40 non-users) during July-August 2021. Respondents were women who cook for their families regularly. This paper based on a cross-sectional analysis of nine socio-economic and demographic parameters that may influence biogas uptake in Western Bangladesh. The dependent variable, biogas cooking fuel adoption status, was modeled as a dichotomous variable. To evaluate the relationship between independent variables with the dependent variable (biogas user and no-user), bivariate descriptive analysis (t-test for continuous data and chi-square test for categorical data) was performed. Then, a binary regression model was chosen to determine the adjusted effect of independent variables on biogas adoption decisions. The study found that the demographic factors such as income status of the women, education of household head, family size and total family income significantly and positively influence biogas adoption decisions. Contrary to the hypothesis, access to internet and total land area owned by the family show negative relation with biogas cooking fuel adoption status of the household. The outcome of this research added evidence to support energy policy with giving emphasis on subsidy, and adult education in rural areas. SAARC J. Agric., 20(2): 261-272 (2022)